Silicon dioxide-lithium lanthanum zirconium oxide heterogeneous ceramic reinforced polymer composite electrolyte as well as preparation method and application thereof

By constructing a vertical continuous silicon dioxide-lithium lanthanum zirconium oxygen ceramic structure in lithium lanthanum zirconium oxygen nanoparticle reinforced polymer electrolyte, the problems of low ionic conductivity and poor cycling performance of lithium lanthanum zirconium oxygen nanoparticle electrolyte are solved, and the problem of low ionic conductivity and poor cycling performance of lithium lanthanum zirconium oxygen nanoparticle electrolyte is achieved. Lithium metal battery with high energy density and safety.

CN119170866APending Publication Date: 2024-12-20DONGHUA UNIV
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411280027.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-12
Publication Date
2024-12-20

AI Technical Summary

Technical Problem

The existing lithium lanthanum zirconium oxygen (LLZO) nanoparticle reinforced polymer solid electrolyte has low ionic conductivity and poor long cycle performance, resulting in insufficient energy density and safety of lithium metal batteries.

Method used

The ordered silicon dioxide (SiO2) network was generated as a template by frozen casting, and vertically continuous lithium lanthanum zirconium oxygen (LLZO) ceramic structure was constructed, and in-situ polymerization was carried out on the lithium metal negative electrode to prepare three-dimensional vertical continuous silicon dioxide- Lithanum zirconium oxygen heterocemic reinforced polymer composite electrolyte.

Benefits of technology

It improves the conductivity and electrochemical performance of lithium ions, reduces the interface resistance of the battery, and enhances the cycling stability and safety of lithium metal batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119170866A_ABST
    Figure CN119170866A_ABST
Patent Text Reader

Abstract

The invention discloses a silicon dioxide-lithium lanthanum zirconium oxide heterogeneous ceramic reinforced polymer composite electrolyte as well as a preparation method and application thereof. A silicon dioxide ordered network is generated through freeze casting, the silicon dioxide ordered network is used as a framework for in-situ derivation to construct vertical and continuous LLZO ceramic, and the LLZO ceramic is combined on a lithium metal negative electrode for in-situ polymerization to prepare the lithium-ion battery with good electrode-electrolyte interface contact and high electrochemical performance. And the SiO2-LLZO heterogeneous ceramic reinforced polymer composite solid electrolyte has high ionic conductivity and excellent long cycle performance. The excellent performance of the electrolyte benefits from the following two points: (1) the vertically arranged LLZO reduces the tortuosity of ion transmission and accelerates the transmission of ions between two electrodes; and (2) the LLZO synthesized in situ by taking SiO2 as a carrier forms a continuous ion transmission path, so that the condition that ions need to pass through a multiphase transmission process among an interface, a polymer and an interface is avoided, and the conduction of lithium ions is accelerated.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of solid-state lithium metal batteries, and in particular relates to a preparation method and application of a three-dimensional vertical continuous silicon dioxide-lithium lanthanum zirconium oxygen heterogeneous ceramic reinforced polymer composite electrolyte. Background Art

[0002] With the rapid development of electric vehicles, hybrid vehicles and other fields, the traditional lithium-ion battery composed of graphite anode and organic liquid electrolyte has limited energy density and can no longer meet the growing energy demand of advanced electrochemical energy storage systems. It is urgent to seek batteries with higher energy density. As we all know, metallic lithium has an ultra-high energy density (3860mAh g -1 ) and the lowest redox potential (-3.04V) have become one of the most promising negative electrode materials. However, organic liquid electrolytes are prone to side reactions with lithium metal negative electrodes, resulting in uncontrollable dendrite growth. The continuous growth of lithium dendrites will deplete the electrolyte, thicken the solid electrolyte interface (SEI), and cause internal short circuits in the battery, causing serious safety problems. Strategies to address these challenges include: introducing solid electrolytes, designing artificial interface layers, and developing electrolyte additives. Among them, solid electrolytes are used to replace organic liquid electrolytes because they can effectively inhibit the growth of lithium dendrites.

[0003] In order to obtain high-performance lithium metal batteries, solid electrolytes need to have high ionic conductivity, wide electrochemical working window, excellent interface stability and high mechanical strength. To this end, researchers have conducted in-depth research on solid electrolytes and divided solid electrolytes into organic electrolytes, inorganic electrolytes and organic-inorganic composite electrolytes. Organic electrolytes are easy to process and have good contact with the electrode interface, but they have low strength, low ionic conductivity, poor high temperature resistance, and safety issues such as flammability and easy short circuit. Inorganic electrolytes mainly refer to ceramic electrolytes. This type of electrolyte has high ionic conductivity (>10 -4 S cm -1 ) and a wide electrochemical stability window (>4.5V), but ceramic electrolytes are brittle, difficult to process, and have poor interfacial contact with the lithium negative electrode, resulting in slow solid-state interfacial charge transfer and large interfacial impedance. The organic-inorganic composite electrolyte prepared by introducing inorganic fillers into polymers combines the advantages of a single electrolyte and has excellent mechanical strength, high temperature resistance and high ionic conductivity. However, the random distribution of inorganic fillers in polymers can lead to problems such as high tortuosity and discontinuous transmission paths during ion transmission, thereby affecting the electrochemical performance of lithium metal batteries.

[0004] The study found that the microstructure of ceramics and their arrangement in the polymer matrix have a significant impact on the performance of composite electrolytes. Generally speaking, continuous structures (such as nanosheets) have higher ionic conductivity than discontinuous structures (such as nanoparticles), and the ordered arrangement of inorganic fillers can further improve ionic conductivity compared to disordered arrangements. The currently developed disordered lithium lanthanum zirconium oxide (LLZO) nanoparticle-enhanced polymer electrolytes still face bottlenecks and problems of low ionic conductivity and poor long-cycle performance at 60°C, which restricts their practical application in composite electrolytes.

[0005] In response to the above problems, it has become a great challenge to develop an ordered LLZO ceramic reinforced polymer electrolyte with simple preparation method, high ionic conductivity and long-term cycle stability. Summary of the invention

[0006] In order to solve the problem of low ionic conductivity of LLZO nanoparticle-reinforced polymer solid electrolytes, the present invention provides a method for preparing a three-dimensional vertically continuous silica-lithium lanthanum zirconium oxide ceramic reinforced polymer composite electrolyte, and applies it to the field of solid-state lithium metal batteries. First, an ordered SiO2 network is generated by freeze casting. Secondly, the SiO2 network is used as a framework to in-situ derive a vertically continuous lithium lanthanum zirconium oxide (LLZO) ceramic. Finally, combined with an in-situ polymerization method on a lithium metal negative electrode, a silica-lithium lanthanum zirconium oxide heterogeneous ceramic reinforced polymer composite solid electrolyte with high ionic conductivity and good electrode-electrolyte interface contact is prepared.

[0007] The high ionic conductivity of the solid electrolyte prepared by the present invention is derived from the vertically arranged LLZO as a skeleton filler, which not only improves the mechanical strength of the polymer, but also reduces the tortuosity of ion transmission, thereby accelerating the transmission of ions between the positive and negative electrodes. In addition, the in-situ derivatization constructs a continuous LLZO to form a continuous ion transmission path, thereby accelerating the conduction of lithium ions. The electrochemical performance of the solid electrolyte is improved by regulating the microstructure and arrangement of LLZO and combining the in-situ polymerization method.

[0008] The technical solution adopted by the present invention is as follows:

[0009] A silica-lithium lanthanum zirconium oxide ceramic reinforced polymer composite electrolyte, wherein an ordered SiO2 network with a vertical pore structure provides a template for the vertical continuous arrangement of LLZO nanoparticles inside the composite material, and the lithium ion conductor LLZO ceramic filler is vertically and continuously arranged to obtain a silica-lithium lanthanum zirconium oxide inorganic filler; the inorganic filler and polyethylene glycol methyl ether acrylate monomer are in-situ polymerized on the surface of a lithium negative electrode to obtain a three-dimensional vertically continuous silica-lithium lanthanum zirconium oxide heterogeneous ceramic reinforced polymer composite electrolyte.

[0010] A method for preparing a silicon dioxide-lithium lanthanum zirconium oxygen heterogeneous ceramic reinforced polymer composite electrolyte comprises the following steps:

[0011] Step (1) Take a 10 ml glass bottle, designated as bottle 1, for preparing a polyether precursor solution; first, add 2 g of polyethylene glycol methyl ether acrylate monomer and 0.02 g of azobisisobutyronitrile as a thermal initiator to bottle 1, transfer the glass bottle to a glove box, add 0.4 g of lithium bistrifluoromethanesulfonyl imide, stir until the lithium salt is completely dissolved, and place in the glove box for later use;

[0012] Step (2) adding hexadecyltrimethylammonium bromide as a cationic surfactant to a mixed solution of methyltrimethoxysilane, tetraethyl orthosilicate, ethanol, polyvinyl alcohol and water; after mixing evenly at 30°C, adding an appropriate amount of ammonia water to accelerate the condensation reaction after the hydrolysis reaction, and after 35 minutes, dropping an appropriate amount of dilute hydrochloric acid to remove the ammonia water in the solution; taking an appropriate amount of liquid and spreading it on a polytetrafluoroethylene plate, unidirectionally freezing and oriented it with liquid nitrogen, and then transferring it to a freeze dryer for freeze drying for 24 hours, and sintering the obtained film at 850°C for 2 hours, thereby preparing a SiO2 film with a vertical pore structure;

[0013] Step (3) taking the SiO2 film prepared in step (2) as a template, fully soaking it in the LLZO precursor solution for more than 5 hours, drying the SiO2 film filled with the precursor solution at 60°C for 10-12 hours, controlling the mass ratio of the film after drying to the mass ratio of the pure SiO2 film to the designed value, sintering at 850°C for 2 hours, and obtaining a three-dimensional vertical continuous silica-lithium lanthanum zirconium oxide heterogeneous ceramic reinforced polymer composite electrolyte.

[0014] The invention discloses an application of a silicon dioxide-lithium lanthanum zirconium oxygen heterogeneous ceramic reinforced polymer composite electrolyte for preparing a solid-state lithium metal battery. The solid-state lithium metal battery comprises a positive electrode and a negative electrode.

[0015] Based on the three-dimensional vertical continuous silicon dioxide-lithium lanthanum zirconium oxygen heterogeneous ceramic reinforced polymer composite electrolyte of the present invention, a solid-state lithium metal battery is prepared, comprising the following steps:

[0016] Step (4) Spreading the silica-lithium lanthanum zirconium oxide heterogeneous ceramic reinforced polymer composite electrolyte on the lithium metal negative electrode, dripping 60 μl of the solution in bottle 1, and letting it stand for 0.5-1 hour; then placing it on a hot plate and heating it at a temperature of 60-65° C. for 2-3 hours to complete the integrated in-situ preparation process of the negative electrode-polymer solid electrolyte;

[0017] Step (5) Solid-state lithium metal battery assembly: According to the button cell assembly method, take out the 2050 type battery shell, place the negative electrode shell at the bottom, and put in the spring, gasket, integrated electrolyte, positive electrode and positive electrode shell in sequence, and finally use a packaging machine to package the battery.

[0018] The present invention prepares a SiO2 network with a vertical pore structure through freeze casting technology, and uses it as a template to prepare a series of silicon dioxide-lithium lanthanum zirconium oxide ceramic composite materials with different content ratios. The vertically arranged LLZO provides a directional channel for ion transmission, reduces the tortuosity of ion transmission, and accelerates the transmission of ions between the two electrodes. In addition, the microstructure of the ceramic composite material is adjusted by adjusting the content of LLZO to provide a continuous transmission path for lithium ions, further accelerating ion transmission, and the ion conductivity at 60°C reaches 1.4×10 -4 S cm -1 At the same time, the electrolyte prepared by in-situ polymerization on the electrode has good electrode-electrolyte interface contact and reduced interface resistance, and the solid-state lithium metal battery assembled with it has excellent electrochemical performance.

[0019] In the solid-state lithium metal battery of the prior art, LLZO nanoparticles are usually used as inorganic fillers to reinforce polymers to prepare composite electrolytes. When randomly arranged nanoparticles are used as fillers, the tortuosity of ion transmission is large, and the gaps between the particles are filled with polymer matrix, which cannot provide a continuous transmission path for ions, resulting in low ion conductivity of the electrolyte (<10 -5 S cm -1 ). In addition, the poor contact between the composite electrolyte synthesized non-in situ and the electrode not only makes the electrode-electrolyte interface impedance large, but also causes uneven local current density during battery cycling, resulting in uneven deposition of lithium ions at the negative electrode, accelerating the growth of lithium dendrites, and the dendrites piercing the electrolyte and connecting to the positive electrode, thereby increasing the risk of battery short circuit.

[0020] Compared with the prior art, the present invention combines freeze casting technology with in-situ polymerization to prepare a LLZO ceramic reinforced composite solid electrolyte that is perpendicular and continuous to the electrode in three-dimensional space, which can not only reduce the tortuosity of ion transmission, but also provide a continuous transmission path for ions, which is beneficial to improve the ionic conductivity of the electrolyte (>10 -4 S cm -1 ). Moreover, the method of preparing the electrolyte by in-situ polymerization on the negative electrode can improve the interface contact between the electrolyte and the electrode to the greatest extent, greatly reduce the interface resistance of the battery, and improve the electrochemical performance of the battery.

[0021] Principle of the invention: The invention prepares a three-dimensional vertical continuous silica-lithium lanthanum zirconium oxide ceramic reinforced polymer solid electrolyte by a simple freeze casting and in-situ derivatization method. The LLZO, which is perpendicular to the electrode and presents a continuous structure, reduces the tortuosity of ion transmission and provides a continuous transmission path for lithium ions. The prepared ceramic filler is polymerized in-situ on the negative electrode to form a composite electrolyte, which greatly reduces the interfacial resistance of the battery. This reasonable invention design enables the battery to have better electrochemical performance during the cycle process, and can also provide a certain theoretical basis for the structural design of other new heterogeneous ceramic reinforced composite solid electrolytes.

[0022] Compared with the prior art, the effects of the present invention are as follows:

[0023] (1) The preparation method of three-dimensional vertical continuous silica-lithium lanthanum zirconium oxide ceramic reinforced polymer composite solid electrolyte is simple. The vertical arrangement of inorganic fillers in three-dimensional space can reduce the tortuosity of ion transmission, making the composite electrolyte have high ionic conductivity.

[0024] (2) The continuous structure of LLZO provides a continuous transmission path for ions, further improving the ionic conductivity of the electrolyte.

[0025] (3) The in-situ polymerization method on the electrode can significantly improve the interfacial compatibility of the electrode-electrolyte and reduce the interfacial resistance, thereby enabling the battery to have excellent electrochemical performance during cycling. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 This is a scanning electron microscope image of the SiO2 network containing a vertical pore structure provided in Example 1 of the present invention.

[0027] Figure 2 The scanning electron microscope images of different LLZO ceramic contents provided in Examples 1, 2, and 3 of the present invention. 10 SEM plane and cross-sectional images of ZO1; (b) the vertical column is Si 10 SEM plane and cross-sectional images of ZO2; (c) the vertical column is Si 10 SEM plan and cross-sectional images of ZO3.

[0028] Figure 3 This is an image of the composite solid electrolyte obtained by in-situ polymerization on the negative electrode provided in Example 1 and its scanning electron microscope image.

[0029] Figure 4 The ionic conductivity of the composite solid electrolyte provided in Examples 1, 2, 3 and Comparative Example 1 of the present invention at different temperatures.

[0030] Figure 5Long cycle test curves of lithium-lithium symmetrical batteries assembled with the composite solid electrolyte and Li sheets provided in Examples 1, 2, 3 and Comparative Example 1 of the present invention.

[0031] Figure 6 Long cycle test curves of full batteries assembled with the composite solid electrolyte and lithium iron phosphate provided in Examples 1, 2, 3 and Comparative Example 1 of the present invention. DETAILED DESCRIPTION

[0032] In order to better understand the present invention, the content of the present invention is further explained below in conjunction with the embodiments, but the content of the present invention is not limited to the following embodiments.

[0033] In an organic-inorganic composite electrolyte system, the microstructure of the inorganic matter and its arrangement in the polymer matrix will affect the electrochemical properties of the composite electrolyte. When the LLZO nanoparticles prepared by the prior art are used as inorganic fillers, the ion transmission tortuosity is high, the transmission path is discontinuous, and the assembled lithium symmetric battery is prone to short circuit when cycling at 60°C, resulting in low ion conductivity and poor long-cycle performance of the prepared electrolyte. In order to solve this problem, we designed the LLZO ceramic filler into a vertical continuous structure to reduce the tortuosity during lithium ion transmission and enable continuous transmission. In addition, for electrolytes synthesized non-in situ, the large interface resistance between the electrolyte and the electrode will affect the electrochemical performance of the battery. In order to reduce the interface resistance, we chose the method of in situ polymerization on the negative electrode and developed an integrated electrolyte-electrode system, thereby solving the problem of large electrolyte-electrode interface resistance.

[0034] The present invention prepares a three-dimensional vertical continuous silica-lithium lanthanum zirconium oxide ceramic reinforced polymer composite solid electrolyte by a simple freeze casting and in-situ derivatization method. The content of Si-O-Si bonds in the SiO2 network will affect the microstructure of the SiO2 network, and then affect its electrochemical performance. Because in the process of preparing the SiO2 ordered network by freeze casting, the Si-O-Si bonds in the SiO2 network will hinder the growth of ice crystals, reduce the vertical pore structure of the prepared SiO2 film, and then reduce the path of vertical ion transmission, which is not conducive to ion transmission. Figure 1 As shown in the figure, the film structure prepared by reacting the SiO2 precursor solution at 30°C for 35 minutes is complete and contains many vertical pores. The complete SiO2 film is used as a framework, and LLZO is derived inside it. The content of LLZO will also affect the ion transmission path. When the LLZO content is low, the ceramic particles are randomly distributed along the pore walls of the SiO2 vertical pores, and the particles cannot contact each other; when the content is too high, the particles will agglomerate and cracks will appear between the clusters. After experimental verification, the optimal mass ratio of SiO2 to LLZO is 10:2. Finally, the amount of the in-situ polymerized precursor liquid dripped on the negative electrode is 60μlcm -2, the solid electrolyte after polymerization is about 350μm.

[0035] The present invention uses a SiO2 framework containing a vertical pore structure as a load template for the LLZO precursor. During the sintering process, the LLZO nanoparticles are arranged vertically along the pore wall, thereby forming an LLZO nanosheet layer perpendicular to the electrode. In addition, the density of the LLZO nanoparticles is controlled by adjusting the concentration of the LLZO precursor solution, providing a continuous transmission path for lithium ions and accelerating the conduction of lithium ions, thereby preparing a three-dimensional vertical continuous silicon dioxide-lithium lanthanum zirconium oxide ceramic reinforced polymer composite solid electrolyte with high ionic conductivity.

[0036] A silica-lithium lanthanum zirconium oxide heterogeneous ceramic reinforced polymer composite electrolyte, wherein the ordered SiO2 network with a vertical pore structure provides a template for the vertical continuous arrangement of LLZO nanoparticles inside the composite material, and the lithium ion conductor LLZO ceramic filler is vertically and continuously arranged to obtain a silica-lithium lanthanum zirconium oxide inorganic filler; the inorganic filler is in situ polymerized with polyethylene glycol methyl ether acrylate monomer on the surface of the lithium negative electrode to obtain a three-dimensional vertical continuous silica-lithium lanthanum zirconium oxide heterogeneous ceramic reinforced polymer composite electrolyte, which reduces the electrode-electrolyte interface impedance and improves the electrochemical performance of lithium metal batteries. The vertically and continuously arranged lithium ion conductor LLZO ceramic filler can not only reduce the tortuosity of ion transmission, but also provide a continuous transmission path for lithium ions, which helps to accelerate the migration of lithium ions in the electrolyte.

[0037] Preferably, the LLZO constructed by in-situ derivatization on the SiO2 ordered network of the present invention is used as an inorganic filler of the composite electrolyte, which not only has a strong ion-conducting ability but also increases the mechanical strength of the solid electrolyte.

[0038] Preferably, the preparation conditions of the SiO2 ordered network framework of the present invention are reaction at 30°C for 35 minutes.

[0039] Preferably, the mass ratio of the SiO2 ordered network to the LLZO nanoparticles of the present invention is 10:2.

[0040] Preferably, the silica-lithium lanthanum zirconium oxide inorganic filler of the present invention is in-situ polymerized with 60 μl of polyethylene glycol methyl ether acrylate monomer on the surface of the lithium negative electrode. During the polymerization process, it needs to be left to stand for 0.5-1 hour and then heated on a 65° C. hot stage for 2-3 hours.

[0041] A method for preparing a three-dimensional vertical continuous silicon dioxide-lithium lanthanum zirconium oxygen heterogeneous ceramic reinforced polymer composite electrolyte comprises the following steps:

[0042] Step (1) Take a 10 ml glass bottle, designated as bottle 1, for preparing a polyether precursor solution; first, add 2 g of polyethylene glycol methyl ether acrylate monomer and 0.02 g of azobisisobutyronitrile as a thermal initiator to bottle 1, transfer the glass bottle to a glove box, add 0.4 g of lithium bistrifluoromethanesulfonyl imide, stir until the lithium salt is completely dissolved, and place in the glove box for later use;

[0043] Step (2) adding hexadecyltrimethylammonium bromide as a cationic surfactant to a mixed solution of methyltrimethoxysilane, tetraethyl orthosilicate, ethanol, polyvinyl alcohol and water; after mixing evenly at 30°C, adding an appropriate amount of ammonia water to accelerate the condensation reaction after the hydrolysis reaction, and after 35 minutes, dropping an appropriate amount of dilute hydrochloric acid to remove the ammonia water in the solution; taking an appropriate amount of liquid and spreading it on a polytetrafluoroethylene plate, unidirectionally freezing and oriented it with liquid nitrogen, and then transferring it to a freeze dryer for freeze drying for 24 hours, and sintering the obtained film at 850°C for 2 hours, thereby preparing a SiO2 film with a vertical pore structure;

[0044] Step (3) taking the SiO2 film prepared in step (2) as a template, fully soaking it in the LLZO precursor solution for more than 5 hours, drying the SiO2 film filled with the precursor solution at 60°C for 10-12 hours, controlling the mass ratio of the film after drying to the mass ratio of the pure SiO2 film to the designed value, sintering at 850°C for 2 hours, and obtaining a three-dimensional vertical continuous silica-lithium lanthanum zirconium oxide heterogeneous ceramic reinforced polymer composite electrolyte.

[0045] The LLZO precursor solution in the above step (3) is prepared by LiNO3, Al(NO3)3·9H2O, La(NO3)3·6H2O, acetic acid, and Zr(OCH2CH2CH3)4 in a certain molar ratio.

[0046] The polyether precursor solution of the present invention is a mixture of polyethylene glycol acrylate (PEGMEA), azobisisobutyronitrile (AIBN), and lithium bistrifluoromethanesulfonyl imide (LiTFSI). PEGMEA is a monomer that can form an ether polymer at a certain temperature, and the flexible chain in the polyether is conducive to lithium ion migration. AIBN is a thermal initiator used to initiate the polymerization reaction of the monomer, and its content is 1wt% of PEGMEA. LiTFSI is a lithium salt used to increase the lithium ion concentration in the polymer, and its content is 20wt% of PEGMEA. The in-situ polymerization method is used to make the electrolyte and the electrode have better interface contact, thereby greatly reducing the interface impedance of ion transmission.

[0047] The invention discloses an application of a silicon dioxide-lithium lanthanum zirconium oxygen heterogeneous ceramic reinforced polymer composite electrolyte for preparing a solid-state lithium metal battery. The solid-state lithium metal battery comprises a positive electrode and a negative electrode.

[0048] Based on the three-dimensional vertical continuous silicon dioxide-lithium lanthanum zirconium oxygen heterogeneous ceramic reinforced polymer composite electrolyte of the present invention, a solid-state lithium metal battery is prepared, comprising the following steps:

[0049] Step (4) Spreading the silica-lithium lanthanum zirconium oxide heterogeneous ceramic reinforced polymer composite electrolyte on the lithium metal negative electrode, dripping 60 μl of the solution in bottle 1, and letting it stand for 0.5-1 hour; then placing it on a hot plate and heating it at a temperature of 60-65° C. for 2-3 hours to complete the integrated in-situ preparation process of the negative electrode-polymer solid electrolyte;

[0050] Step (5) Solid-state lithium metal battery assembly: According to the button cell assembly method, take out the 2050 type battery shell, place the negative electrode shell at the bottom, and put in the spring, gasket, integrated electrolyte, positive electrode and positive electrode shell in sequence, and finally use a packaging machine to package the battery.

[0051] The present invention aims at the problems of low ion conductivity and long-cycle instability in lithium lanthanum zirconium oxide (LLZO) nanoparticle-enhanced polymer solid electrolyte. The present invention generates an ordered network of silicon dioxide (SiO2) by freeze casting, uses it as a framework to in-situ derive and construct a vertically continuous LLZO ceramic, and combines it with an in-situ polymerization method on a lithium metal negative electrode to prepare a SiO2-LLZO heterogeneous ceramic-enhanced polymer composite solid electrolyte with good electrode-electrolyte interface contact, high ion conductivity and excellent long-cycle performance. The excellent performance of the electrolyte is due to the following two points: (1) the vertically arranged LLZO reduces the tortuosity of ion transmission and accelerates the transmission of ions between the two electrodes; (2) the LLZO synthesized in-situ with SiO2 as a carrier forms a continuous ion transmission path, avoiding the need for ions to pass through the multiphase transmission process between the interface-polymer-interface, thereby accelerating the conduction of lithium ions.

[0052] Example 1

[0053] Step (1) Take a 10 ml glass bottle and mark it as bottle 1 for preparing the polyether precursor solution. First, add 2 g of PEGMEA monomer (average number average molecular weight M n ~480) and 0.02g of azobisisobutyronitrile as a thermal initiator, transfer the glass bottle into a glove box, add 0.4g of lithium bistrifluoromethanesulfonyl imide (LiTFSI), stir until the lithium salt is completely dissolved, and place it in the glove box for later use.

[0054] Step (2) Add hexadecyltrimethylammonium bromide as a cationic surfactant to a mixed solution of methyltrimethoxysilane, tetraethyl orthosilicate, ethanol, polyvinyl alcohol (PVA), and water. After mixing evenly at 30°C, add an appropriate amount of ammonia water to accelerate the condensation reaction after the hydrolysis reaction. After 35 minutes, drop an appropriate amount of dilute hydrochloric acid to remove the ammonia water in the solution. Take an appropriate amount of liquid and spread it on a polytetrafluoroethylene plate. After unidirectional freezing orientation with liquid nitrogen, transfer it to a freeze dryer and freeze-dry it for 24 hours. The obtained film is sintered at 850°C for 2 hours to prepare a SiO2 film with a vertical pore structure.

[0055] Step (3) takes the SiO2 film prepared in step (2) as a template, fully soaks it in the LLZO precursor solution for more than 5 hours, dries the SiO2 film filled with the precursor solution at 60°C for 10-12 hours, ensures that the film quality after drying is 110% of the quality of the pure SiO2 film, and sinters at 850°C for 2 hours to obtain a three-dimensional vertical continuous silica-lithium lanthanum zirconium oxide composite ceramic.

[0056] Step (4) Spread the silicon dioxide-lithium lanthanum zirconium oxide composite ceramic on the lithium metal negative electrode, drip 60 μl of the solution in bottle 1, and let it stand for 0.5-1 hour. Then place it on a hot plate and heat it at 60-65° C. for 2-3 hours to complete the integrated in-situ preparation process of the negative electrode-polymer solid electrolyte.

[0057] Step (5) Solid-state lithium metal battery assembly: According to the button cell assembly method, take out the 2050 type battery shell, place the negative electrode shell at the bottom, and put in the spring, gasket, integrated electrolyte, positive electrode and positive electrode shell in sequence, and finally use a packaging machine to package the battery.

[0058] Example 2

[0059] Step (1) Take a 10 ml glass bottle and record it as bottle 1, which is used to prepare the polyether precursor solution. First, add 2 g of PEGMEA monomer (average number average molecular weight Mn ~ 480) and 0.02 g of azobisisobutyronitrile as a thermal initiator into bottle 1, transfer the glass bottle into a glove box, add 0.4 g of lithium bistrifluoromethanesulfonyl imide (LiTFSI), stir until the lithium salt is completely dissolved, and place it in the glove box for later use.

[0060] Step (2) Add hexadecyltrimethylammonium bromide as a cationic surfactant to a mixed solution of methyltrimethoxysilane, tetraethyl orthosilicate, ethanol, polyvinyl alcohol (PVA), and water. After mixing evenly at 30°C, add an appropriate amount of ammonia water to accelerate the condensation reaction after the hydrolysis reaction. After 35 minutes, drop an appropriate amount of dilute hydrochloric acid to remove the ammonia water in the solution. Take an appropriate amount of liquid and spread it on a polytetrafluoroethylene plate. After unidirectional freezing orientation with liquid nitrogen, transfer it to a freeze dryer and freeze-dry it for 24 hours. The obtained film is sintered at 850°C for 2 hours to prepare a SiO2 film with a vertical pore structure.

[0061] Step (3) takes the SiO2 film prepared in step (2) as a template, fully soaks it in the LLZO precursor solution for more than 5 hours, dries the SiO2 film filled with the precursor solution at 60°C for 10-12 hours, ensures that the mass of the film after drying is 120% of the mass of the pure SiO2 film, and sinters at 850°C for 2 hours to obtain a three-dimensional vertical continuous silica-lithium lanthanum zirconium oxide composite ceramic.

[0062] Step (4) Spread the silicon dioxide-lithium lanthanum zirconium oxide composite ceramic on the lithium metal negative electrode, drip 60 μl of the solution in bottle 1, and let it stand for 0.5-1 hour. Then place it on a hot plate and heat it at 60-65° C. for 2-3 hours to complete the integrated in-situ preparation process of the negative electrode-polymer solid electrolyte.

[0063] Step (5) Solid-state lithium metal battery assembly: According to the button cell assembly method, take out the 2050 type battery shell, place the negative electrode shell at the bottom, and put in the spring, gasket, integrated electrolyte, positive electrode and positive electrode shell in sequence, and finally use a packaging machine to package the battery.

[0064] Example 3

[0065] Step (1) Take a 10 ml glass bottle and record it as bottle 1, which is used to prepare the polyether precursor solution. First, add 2 g of PEGMEA monomer (average number average molecular weight Mn ~ 480) and 0.02 g of azobisisobutyronitrile as a thermal initiator into bottle 1, transfer the glass bottle into a glove box, add 0.4 g of lithium bistrifluoromethanesulfonyl imide (LiTFSI), stir until the lithium salt is completely dissolved, and place it in the glove box for later use.

[0066] Step (2) Add hexadecyltrimethylammonium bromide as a cationic surfactant to a mixed solution of methyltrimethoxysilane, tetraethyl orthosilicate, ethanol, polyvinyl alcohol (PVA), and water. After mixing evenly at 30°C, add an appropriate amount of ammonia water to accelerate the condensation reaction after the hydrolysis reaction. After 35 minutes, drop an appropriate amount of dilute hydrochloric acid to remove the ammonia water in the solution. Take an appropriate amount of liquid and spread it on a polytetrafluoroethylene plate. After unidirectional freezing orientation with liquid nitrogen, transfer it to a freeze dryer and freeze-dry it for 24 hours. The obtained film is sintered at 850°C for 2 hours to prepare a SiO2 film with a vertical pore structure.

[0067] Step (3) takes the SiO2 film prepared in step (2) as a template, fully soaks it in the LLZO precursor solution for more than 5 hours, dries the SiO2 film filled with the precursor solution at 60°C for 10-12 hours, ensures that the film quality after drying is 130% of the quality of the pure SiO2 film, and sinters at 850°C for 2 hours to obtain a three-dimensional vertical continuous silica-lithium lanthanum zirconium oxide composite ceramic.

[0068] Step (4) Spread the silicon dioxide-lithium lanthanum zirconium oxide composite ceramic on the lithium metal negative electrode, drip 60 μl of the solution in bottle 1, and let it stand for 0.5-1 hour. Then place it on a hot plate and heat it at 60-65° C. for 2-3 hours to complete the integrated in-situ preparation process of the negative electrode-polymer solid electrolyte.

[0069] Step (5) Solid-state lithium metal battery assembly: According to the button cell assembly method, take out the 2050 type battery shell, place the negative electrode shell at the bottom, and put in the spring, gasket, integrated electrolyte, positive electrode and positive electrode shell in sequence, and finally use a packaging machine to package the battery.

[0070] Comparative Example 1

[0071] Step (1) Take a 10 ml glass bottle and record it as bottle 2, which is used to prepare a mixed solution of polyether precursor and LLZO ceramic particles. First, add 2 g of PEGMEA monomer (average number average molecular weight Mn ~ 480), 0.02 g of azobisisobutyronitrile as a thermal initiator and 0.06 g of LLZO ceramic particles into bottle 1, transfer the glass bottle into a glove box, add 0.4 g of lithium bistrifluoromethanesulfonyl imide (LiTFSI), stir until the lithium salt is completely dissolved, and place it in the glove box for later use.

[0072] Step (2) Add hexadecyltrimethylammonium bromide as a cationic surfactant to a mixed solution of methyltrimethoxysilane, tetraethyl orthosilicate, ethanol, polyvinyl alcohol (PVA), and water. After mixing evenly at 30°C, add an appropriate amount of ammonia water to accelerate the condensation reaction after the hydrolysis reaction. After 35 minutes, drop an appropriate amount of dilute hydrochloric acid to remove the ammonia water in the solution. Take an appropriate amount of liquid and spread it on a polytetrafluoroethylene plate. After unidirectional freezing orientation with liquid nitrogen, transfer it to a freeze dryer and freeze-dry it for 24 hours. The obtained film is sintered at 850°C for 2 hours to prepare a SiO2 film with a vertical pore structure.

[0073] Step (3) SiO2 is spread on the lithium metal negative electrode, and 60 μl of the solution in bottle 2 is dripped in, and the mixture is allowed to stand for 0.5-1 h. The mixture is then placed on a hot plate and heated at 60-65° C. for 2-3 h to complete the in-situ preparation process of the integrated negative electrode-polymer solid electrolyte.

[0074] Step (4) Solid-state lithium metal battery assembly: According to the button cell assembly method, take out the 2050 type battery shell, place the negative electrode shell at the bottom, and put in the spring, gasket, integrated electrolyte, positive electrode and positive electrode shell in sequence, and finally use a packaging machine to package the battery.

[0075] Figure 2 The scanning electron microscope images of different LLZO ceramic contents provided in Examples 1, 2, and 3 of the present invention. 10 SEM plane and cross-sectional images of ZO1; (b) the vertical column is Si10 SEM plane and cross-sectional images of ZO2; (c) the vertical column is Si 10 SEM plan and cross-sectional images of ZO3. Figure 2 (a) It can be seen from the SEM image that the mass ratio of SiO2 to LLZO is 10:1, and there is a vertical pore structure in the SiO2 network.

[0076] Depend on Figure 3 It can be seen that the surface of the silica-lithium lanthanum zirconium oxygen heterogeneous ceramic reinforced polymer composite electrolyte is flat and smooth, and from the cross-sectional view it can be seen that the interior of the ceramic is full of polymer and there are no pores, so the electrolyte prepared in this way has high integrity.

[0077] Depend on Figure 4-6 It can be seen that when the LLZO ceramic particles are random and discontinuous in the pores of the SiO2 film (the sample name is Si 10 ZOp2), the ionic conductivity at 60°C is only 1.14×10 -4 S cm -1 The polarization voltage of the lithium symmetric battery during the cycle is large, and the full battery is cycled less than 30 times at a 0.2C rate, and the discharge specific capacity drops sharply, indicating that the battery's cycle performance is poor.

[0078] Combination Figure 4-6 , within a certain range, the increase of LLZO content is beneficial to improve the ionic conductivity of the electrolyte. When the LLZO ceramic content is 0, the ionic conductivity of the prepared electrolyte is low because SiO2 is non-ion conductive. When the mass ratio of SiO2 to LLZO is 10:2, LLZO is continuously arranged on the SiO2 pore wall. At this time, the ion transmission path is the most continuous and the ionic conductivity is high. When the LLZO content is too high, the ceramic particles will agglomerate, the continuous transmission path will be destroyed, and the ionic conductivity will decrease. The cycle performance of symmetrical cells and full cells can further prove that the continuously arranged LLZO constructed in situ through the SiO2 framework has a great influence on the electrochemical properties of the electrolyte, which provides a new idea for solving the problems of low ionic conductivity and long-cycle instability of polymer solid electrolytes.

[0079] Finally, it should be noted that the above is only a preferred embodiment of the present invention and does not limit the present invention in any form. For those skilled in the art, various changes and modifications can be made to the present invention without departing from the spirit and scope of the present invention, and the present invention is intended to include these changes and modifications.

Claims

1. A silicon dioxide-lithium lanthanum zirconium oxygen heterogeneous ceramic reinforced polymer composite electrolyte, characterized in that: The SiO2 framework with vertical pore structure is used as the loading template of LLZO precursor. The nanoparticles of LLZO precursor are arranged vertically along the pore wall to form LLZO nanosheets perpendicular to the electrode. The density of LLZO nanoparticles can be controlled by adjusting the concentration of LLZO precursor solution. The SiO2 framework with a vertical pore structure provides a template for the vertical continuous arrangement of LLZO nanoparticles inside the composite material, and vertically and continuously arranges the lithium ion conductor LLZO ceramic filler to obtain silica-lithium lanthanum zirconium oxide inorganic filler; the inorganic filler and polyethylene glycol methyl ether acrylate monomer are in situ polymerized on the surface of the lithium negative electrode to obtain a three-dimensional vertical continuous silica-lithium lanthanum zirconium oxide heterogeneous ceramic reinforced polymer composite electrolyte.

2. The silicon dioxide-lithium lanthanum zirconium oxygen heterogeneous ceramic reinforced polymer composite electrolyte according to claim 1, characterized in that: LLZO in situ derived and constructed on SiO2 framework serves as inorganic filler in composite electrolyte.

3. The silicon dioxide-lithium lanthanum zirconium oxygen heterogeneous ceramic reinforced polymer composite electrolyte according to claim 1, characterized in that: The preparation conditions of the SiO2 framework were 30°C and 35 min of reaction.

4. The silicon dioxide-lithium lanthanum zirconium oxygen heterogeneous ceramic reinforced polymer composite electrolyte according to claim 1, characterized in that: The mass ratio of SiO2 framework to LLZO nanoparticles is 10:

2.

5. The silicon dioxide-lithium lanthanum zirconium oxygen heterogeneous ceramic reinforced polymer composite electrolyte according to claim 1, characterized in that: The silica-lithium lanthanum zirconium oxide inorganic filler and 60 μl of polyethylene glycol methyl ether acrylate monomer are in situ polymerized on the surface of the lithium negative electrode. During the polymerization process, it is necessary to stand for 0.5-1 hour and then heat on a 65°C hot plate for 2-3 hours.

6. A method for preparing the silicon dioxide-lithium lanthanum zirconium oxygen heterogeneous ceramic reinforced polymer composite electrolyte according to any one of claims 1 to 5, characterized in that: The following steps are involved: Step (1) Take a 10 ml glass bottle, designated as bottle 1, for preparing a polyether precursor solution; first, add 2 g of polyethylene glycol methyl ether acrylate monomer and 0.02 g of azobisisobutyronitrile as a thermal initiator to bottle 1, transfer the glass bottle to a glove box, add 0.4 g of lithium bistrifluoromethanesulfonyl imide, stir until the lithium salt is completely dissolved, and place in the glove box for later use; Step (2) adding hexadecyltrimethylammonium bromide as a cationic surfactant to a mixed solution of methyltrimethoxysilane, tetraethyl orthosilicate, ethanol, polyvinyl alcohol and water; after mixing evenly at 30°C, adding an appropriate amount of ammonia water to accelerate the condensation reaction after the hydrolysis reaction, and after 35 minutes, dropping an appropriate amount of dilute hydrochloric acid to remove the ammonia water in the solution; taking an appropriate amount of liquid and spreading it on a polytetrafluoroethylene plate, unidirectionally freezing and oriented it with liquid nitrogen, and then transferring it to a freeze dryer for freeze drying for 24 hours, and sintering the obtained film at 850°C for 2 hours, thereby preparing a SiO2 film with a vertical pore structure; Step (3) taking the SiO2 film prepared in step (2) as a template, fully soaking it in the LLZO precursor solution for more than 5 hours, drying the SiO2 film filled with the precursor solution at 60°C for 10-12 hours, controlling the mass ratio of the film after drying to the mass ratio of the pure SiO2 film to the designed value, sintering at 850°C for 2 hours, and obtaining a three-dimensional vertical continuous silica-lithium lanthanum zirconium oxide heterogeneous ceramic reinforced polymer composite electrolyte.

7. A method for preparing a silicon dioxide-lithium lanthanum zirconium oxygen heterogeneous ceramic reinforced polymer composite electrolyte, characterized in that: In the above step (3), the LLZO precursor solution is prepared by LiNO3, Al(NO3)3·9H2O, La(NO3)3·6H2O, acetic acid, and Zr(OCH2CH2CH3)4 in a certain molar ratio.

8. An application of the silicon dioxide-lithium lanthanum zirconium oxygen heterogeneous ceramic reinforced polymer composite electrolyte prepared by claim 6, characterized in that: Used to prepare solid-state lithium metal batteries, which include positive and negative electrodes.

9. The use of the silicon dioxide-lithium lanthanum zirconium oxygen heterogeneous ceramic reinforced polymer composite electrolyte according to claim 8, characterized in that: The preparation of a solid-state lithium metal battery comprises the following steps: Step (4) Spreading the silica-lithium lanthanum zirconium oxide heterogeneous ceramic reinforced polymer composite electrolyte on the lithium metal negative electrode, dripping 60 μl of the solution in bottle 1, and letting it stand for 0.5-1 hour; then placing it on a hot plate and heating it at a temperature of 60-65° C. for 2-3 hours to complete the integrated in-situ preparation process of the negative electrode-polymer solid electrolyte; Step (5) Solid-state lithium metal battery assembly: According to the button cell assembly method, take out the 2050 type battery shell, place the negative electrode shell at the bottom, and put in the spring, gasket, integrated electrolyte, positive electrode and positive electrode shell in sequence, and finally use a packaging machine to package the battery.

Citation Information

Cited By

  • Halide composite solid electrolyte, preparation method thereof, positive plate and battery

    CN121618033A

  • Halide composite solid-state electrolyte, method of making same, positive electrode sheet, and battery

    CN121618033B